Control of Rotary Inverted Pendulum by Using On–Off Type of Cold Gas Thrusters - Yusuf Silik; Ulas Yaman (Actuators, 2020)
This article describes the control of a rotary inverted pendulum utilizing on–off-type cold gas thrusters as the actuators, which have high similarities with thruster actuated spacecrafts with slosh dynamics. The study is completed in three phases. Firstly, a Pulse Width Modulator (PWM) design method is utilized to obtain quasi-linear thrust output from the on–off-type thrusters. Then, a single axis angle controller is designed and tested on the setup along with the PWM scheme. Finally, a pendulum is connected to the other end of the platform and a rotary inverted pendulum (Furuta Pendulum) is constructed. In this way, an inherently unstable, under-actuated, on–off driven system is obtained. For the swing-up motion of the pendulum, an energy-based method is employed. Balancing of the pendulum is achieved by an observer-based state feedback controller under small angle assumption and quasi-linear outputs from the PWM driven thrusters. All of these control methodologies are realized on a real-time target machine. The pendulum is stabilized in seven seconds after five swings, which is comparable to the systems with electric motors.